Sub 3-Hour Marathon Runners for Five Consecutive Decades Demonstrate a Reduced Age-Related Decline in Performance - Lepers, Romuald; Burfoot, Amby; Stapley, Paul J. (Frontiers in Physiology, 2021)
Estimation of the age-related decline in athletic performance by analyzing age-group world record performances presents an inherent limitation because the records generally belong to different individuals. Longitudinal studies describing the changes in performance with advancing age for the same individuals with a consistent training regime is more appropriate to determine age-related changes in performance. The aim of this longitudinal study was to examine the age-related decline in running performance of sub 3-hour marathoners for five consecutive calendar decades. The best marathon performances for each decade from 1970s to 2010s were analyzed for 40 sub 3-hour runners (39 males, 1 female). The cohort mean personal best performance was 2 h 23 min ± 9 min at an age of 28.6 ± 4.7 years. The mean difference in age between the first and the last sub 3-hour marathon races was 32.9 ± 1.6 years. The time difference in marathon performance between the personal best and the worst performance during the fifth decade was 26 min ± 9 min, corresponding to a mean increase of 1 min 4 s per year i.e. a decrease in running speed of 0.67 ± 0.29% per year. These results suggest that with consistent training and racing regimes, it is possible to limit the age-related decline in marathon performance to less than 7% per decade at least until 60 years of age. Further studies are required to verify if such a low rate of age-related decline in endurance performance could be maintained after 60 years of age.